2016
DOI: 10.1007/s00345-016-1835-1
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of decreased E-cadherin expression in patients with upper tract urothelial carcinoma: a multi-institutional study

Abstract: Purpose To assess the role of E-cadherin as prognostic biomarker in upper tract urothelial carcinoma (UTUC) in a large multi-institutional cohort of patients.Methods Immunohistochemistry technique was used to evaluate E-cadherin expression in 678 patients with unilateral, sporadic UTUC treated with RNU. E-cadherin expression was considered decreased if 10 % or more cells had decreased expression (<90 %).ResultsDecreased E-cadherin expression was observed in 353 patients (52.1 %) and was associated with advance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 34 publications
0
24
1
Order By: Relevance
“…Through extensive research, a total of 18 articles, including 17 published articles and our retrospective study, were included in the meta-analysis. 7,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] It is pointed out that although some of articles 6,10,16 selected in their meta-analysis came Patients with sessile tumor architecture exhibited a significantly lower RFS (p = 0.001, log-rank test) and CSS (p = 0.009, log-rank test) rate than patients with papillary tumor architecture. from multi-institutional collaborative database organized by Shariat, they were characterized by different origin of dataset or recruitment period, so included them as different studies in our analysis.…”
Section: Identification and Eligibility Of Relevant Studies In Meta-amentioning
confidence: 99%
See 2 more Smart Citations
“…Through extensive research, a total of 18 articles, including 17 published articles and our retrospective study, were included in the meta-analysis. 7,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] It is pointed out that although some of articles 6,10,16 selected in their meta-analysis came Patients with sessile tumor architecture exhibited a significantly lower RFS (p = 0.001, log-rank test) and CSS (p = 0.009, log-rank test) rate than patients with papillary tumor architecture. from multi-institutional collaborative database organized by Shariat, they were characterized by different origin of dataset or recruitment period, so included them as different studies in our analysis.…”
Section: Identification and Eligibility Of Relevant Studies In Meta-amentioning
confidence: 99%
“…They were published from 2009 10 to 2016. 15 The sample size ranged from 101 to 2477 13 patients, and the mean/median follow-up durations varied from 27 11 to 47.5 7 months. Figure 4(a) shows the pooled results from the random effects model combining the HRs for disease recurrence after surgery.…”
Section: Identification and Eligibility Of Relevant Studies In Meta-amentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, most subsequent studies of larger cohorts have failed to demonstrate an independent association between E-cadherin expression and disease recurrence ( 58 , 59 ). Favaretto et al assessed the clinical significance of lower E-cadherin levels in an international cohort of 678 UTUC patients who were treated with RNU ( 60 ), observing that downregulation of E-cadherin in tumor cells correlated with adverse clinicopathological features. They also confirmed that lower E-cadherin expression was linked to a greater probability of disease recurrence and cancer-specific mortality in UTUC.…”
Section: Introductionmentioning
confidence: 99%
“…About the enhancer of zeste homolog 2 (EZH2), which is a contributor to cell cycle regulation and tumorigenesis, is enhanced in NPC; and ectopic EZH2 overexpression is able to induce invasion of NPC cells, and E-cadherin is reduced [9]. Concerning to E-cadherin, it is concluded that decreased expression of E-cadherin has been established as a feature of epithelial-mesenchymal transition in epithelial malignancies [10]. The trimethylation of lysine 27 on histone H3 (H3K27me3), a transcriptional inhibitory histone modification involving tumorigenesis is methylated by EZH2 [11].…”
Section: Introductionmentioning
confidence: 99%